Internal Illuminance Analysis in UTHM Pagoh Residential College - Mohamad Hanapiah, Norhana Idayu; Rosdi, Masturina Sajidah; Mohd Nasri, Nur Hanisa; Aslila Abd Kadir, (Multidisciplinary Applied Research and Innovation, 2023)
The source of light that is found directly independently from the sky is daylight which helps to increase the illumination in the space for daily living. This study was carried out in order to comprehend the concept of natural lighting, as well as to measure and determine the level of natural illumination in the space of a residential student. Indoor and outdoor illuminance reading recorded concurrently. The illumination reading value will then be recorded by merely employing a lux meter positioned in the designated sections. The main equipment used to determine the intensity of natural lighting for this project is the lux meter. When natural illumination is detected on the lux meter, it will detect and produce a reading value. To test the effectiveness of this project, three residential students were chosen in the same position on different floors which is at 1st floor, 2nd floor and 5th floor for three days, and their readings of natural lighting were taken. As a result, the investigation discovered that the illumination reading values on each floor of the house varied. This study also demonstrates adequate natural lighting can lessen reliance on artificial lighting. According to the study's findings, because the sun always moves from east to west and the houses are at different heights, no house in the same location would receive the same lighting.